Analysis of Logical Fallacy on the Arguments Made by Student from 2019 Indonesian Protests and Riots in Television Debates - Ayu Wiranda; Hamzah Hamzah (English Language and Literature, 2022)
AbstractThis study sought to identify the many sorts of logical fallacies used in Indonesian television debates, notably those made by students who participated in the 2019 protests and rioting there. This is a descriptive study that takes a qualitative approach. In this study, the five categories and sixty-two types of fallacies introduced by Damer's (2009) theory of fallacy classification were used. There were eighteen of the sixty different types identified. First, the results revealed that students consistently violated the acceptability and rebuttal criteria in their arguments, using five different fallacies in each category. Second, with a frequency of 27.98%, poisoning the well was the type of fallacy that students used the most frequently, followed by the two-wrong fallacy with a frequency of 10.29% and manipulation of emotion with a frequency of 8.82%.